2016
DOI: 10.1002/jez.b.22680
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypoxia and Hyperoxia on Growth and Expression of Hypoxia‐Related Genes and Proteins in Spotted Gar Lepisosteus oculatus Larvae and Juveniles

Abstract: We studied the molecular responses to different water oxygen levels in gills and swim bladder of spotted gar (Lepisosteus oculatus), a bimodal breather. Fish at swim-up stage were exposed for 71 days to normoxic, hypoxic, and hyperoxic water conditions. Then, all aquaria were switched to normoxic conditions for recovery until the end of the experiment (120 days). Fish were sampled at the beginning of the experiment, and then at 71 days of exposure and at 8 days of recovery. We first cloned three hypoxia-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…TAN concentrations in the High TAN condition corresponded to a concentration of NH3 of 1.6 mg.L -1 ( half of the LC50, Person-Le Ruyet et al, 1995). Oxygen saturations chosen during the Hyperoxia and Hypoxia conditions were previously described to affect fish physiology and behaviour during chronic exposure without being lethal (Chapman and Mckenzie, 2009;Espmark and Baeverfjord, 2009;Rimoldi et al, 2016). Both concentrations of oxygen and TAN used in the present study were quite extreme but can occasionally occur (or even co-occur) in aquaculture conditions in case of technical failures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAN concentrations in the High TAN condition corresponded to a concentration of NH3 of 1.6 mg.L -1 ( half of the LC50, Person-Le Ruyet et al, 1995). Oxygen saturations chosen during the Hyperoxia and Hypoxia conditions were previously described to affect fish physiology and behaviour during chronic exposure without being lethal (Chapman and Mckenzie, 2009;Espmark and Baeverfjord, 2009;Rimoldi et al, 2016). Both concentrations of oxygen and TAN used in the present study were quite extreme but can occasionally occur (or even co-occur) in aquaculture conditions in case of technical failures.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, fish from High TAN, Hyperoxia and Hypoxia conditions spent less time in the periphery area than control fish, which suggest that they were not displaying anxiety-like behaviour contrary to control fish in response to handling. High TAN, Hyperoxia and Hypoxia are known to directly affect fish survival (Magaud et al, 1997;Person-Le Ruyet and Boeuf, 1998;Shimps et al, 2005;Rimoldi et al, 2016). Indeed, fish survival can be impacted in many ways following their exposure to one of these stressors.…”
Section: Discussionmentioning
confidence: 99%
“…The first experiment consisted of a temperature challenge to the embryos and larvae with temperatures of 33 • C and 36 • C. These temperatures are near the upper thermal limits for larvae of this species [37] and above its optimal incubation temperature (28-30 • C) [86]. In the second experiment, fish were exposed to hypoxia (~30% air saturation) and hyperoxia (117% air saturation; Figure 6), since Lepisosteids can tolerate environments with variable dissolved oxygen levels [77,122,123]. The third experiment consisted of exposure to salinities of 4.0 ppt and 6.0 ppt, because Lepisosteids can tolerate euryhaline environments and little information is available on early life stages under these conditions, especially regarding developmental critical windows.…”
Section: Developmental Stages and Experimental Designmentioning
confidence: 99%
“…Only previous studies (Lauriano et al, 2015;Porteus et al, 2015;Rimoldi et al, 2016;Zaccone et al, 2003) have reported the presence of nNOS in the neuroepithelial cells, the putative oxygen receptor of fish and their associated innervation in the gill, larval skin and respiratory gas bladder in fish. The role of gasotransmitters NO, hydrogen disulphide (H2S), carbon monoxide (CO) has been studied in carotid body O 2 sensing.…”
Section: Introductionmentioning
confidence: 99%
“…No study has yet assessed the role of NO in O 2 chemoreception in air-breathing fishes. Only previous studies (Lauriano et al, 2015;Porteus et al, 2015;Rimoldi et al, 2016;Zaccone et al, 2003) have reported the presence of nNOS in the neuroepithelial cells, the putative oxygen receptor of fish and their associated innervation in the gill, larval skin and respiratory gas bladder in fish. Porteus et al (2015) have also demonstrated that NO has an inhibitory effect on the hypoxic ventilatory response in adult zebrafish, but an excitatory effect on the hypoxic ventilation response of larvae.…”
Section: Introductionmentioning
confidence: 99%